Cytological studies on some Agarics - S.P. LAL, MANISHA SHANKAR and (Indian Phytopathology, 2002)
The nuclear behaviour in the basidium of Agaricus nigrovinosus, Agrocybe broadwayi, Chlorophyllum molybdites and Collybia dryophila is being reported.